A framework for classifying misfits between enterprise resource planning (ERP) systems and business strategies - Tan, Shiang Yen; Idrus, Rosnah; Yusof, Umi Kalsom (Universiti Sains Malaysia, 2011)

(untitled)
Enterprise resource planning (ERP) is a broad set of activities that is supported by multi-module application software that helps manufacturers or other businesses manage their activities. ERP is more than a software package; it includes the efforts and activities to integrate internal and external management information, business process automation and reengineering, and organisation structure streamlining. Thus, ERP eventually leads to an efficient and competitive business. Despite the prominence of ERP systems, approximately three-quarters of ERP projects are deemed as failures. Most failures are attributed to the misfit between pre-loaded business models in the ERP system and business requirements in the real world. This paper introduces a framework to classify ERP misfits into logical categories that provide insights for solution derivation. Subsequently, the classification methods are applied to a case study. Practitioners can use the misfit classification method to derive corresponding actions as solutions for ERP misfits based on their nature or specificity. In addition, the theoretical contribution of the ERP misfit problem is explored to provide information for researchers to determine appropriate theories and concepts explaining this domain.